A bivariate generalized geometric distribution with applications. Issue 11 (3rd June 2017) - Gómez–Déniz, E.; Ghitany, M. E.; Gupta, Ramesh C.
ABSTRACT: This paper proposes a bivariate version of the univariate discrete generalized geometric distribution considered by Gómez–Déniz (2010 ). The proposed bivariate distribution can have a positive or negative correlation coefficient which can be used for modeling bivariate-dependent count data. After discussing some of its properties, maximum likelihood estimation is discussed. Two illustrative examples are given for fitting and demonstrating the usefulness of the new bivariate distribution proposed here.